Cases of possible structural-stratigraphic accumulations in the Oriente Basin, analysis on their accumulation mechanisms and implication for future exploration - Feng Ding; Guangfu Wang; Mingxi Xue; Yu Sun; Yaping Liu; Jianfang Sun; Fayou Li (Energy Geoscience)
Three cases of structural-stratigraphic accumulations in the foredeep zone of the Oriente Basin have been analyzed. The target reservoirs are U and M1 sections of Napo Fm. in the Basin. Seismic amplitude maps are used for sand distribution pattern, and wells interpretation and correlations are applied for fluid distribution and reservoir continuity. These cases show that their oil distribution areas are significantly larger than their structure closures and thus should be structural-stratigraphic traps. But only in one case, lateral stratigraphic/lithological seals can be clearly observed. In the other two, the lateral seals are apparently discontinuous and cannot provide a complete barrier at the up-dip of the structures. Possible factors for the formation of those untypical structural-stratigraphic accumulations are studied, such as formation water flow and water head variations, basin and field structure evolution patterns, oil generation and charging history etc. An integrated mechanism is proposed in this study, where three factors may have acted together. 1) Slow long distance oil migration in LU and M1 reservoirs, due to their lateral discontinuity in the foredeep of the basin. This is supported by the distal estuarine and prodelta depositional environment suggested by previous sedimentological studies. 2) Ongoing secondary oil migration from south to north, caused by southward plunging and destruction of proto accumulations in the southern and middle part of the basin. This structure deformation is in turn caused by differential subsidence between the southern and northern part of the basin. 3) Additional oil supplied from the southern kitchen. The southern source kitchen is still in the oil window and providing pulses of oil charge since the Oligocene. If this mechanism is valid, it would imply that in the southern and northern transition zone of the basin, similar untypical traps should also exist. The area of southern extension of the two untypical accumulation is over 50 km2, while within the basin, the transition zone of differential basin subsidence with distal and thus discontinuous LU and M1 reservoirs covers an area over 2000 km2. These findings suggest a new and potentially extensive play concept with significant exploration potential in the Oriente Basin.